Influence of placental and peripheral malaria exposure in fetal life on cardiometabolic traits in adult offspring. Issue 2 (4th April 2022) - Grunnet, Louise G; Bygbjerg, Ib C; Mutabingwa, Theonest K; Lajeunesse-Trempe, Fanny; Nielsen, Jannie; Schmiegelow, Christentze; Vaag, Allan A; Ramaiya, Kaushik; Christensen, Dirk L
Abstract : Introduction: Fetal malaria exposure may lead to intrauterine growth restriction and increase the risk of developing diabetes and cardiovascular diseases in adulthood. We investigated the extent to which fetal peripheral and placental malaria exposure impacts insulin sensitivity and secretion, body composition and cardiometabolic health 20 years after in utero malaria exposure. Research design and methods: We traced 101 men and women in Muheza district, Tanga region whose mothers participated in a malaria chemosuppression during a pregnancy study in 1989–1992. All potential participants were screened for malaria, hepatitis B and HIV to ascertain study eligibility. Seventy-six individuals (44 men, 32 women) were included in this cohort study. The participants underwent a thorough clinical examination including anthropometric measurements, ultrasound scanning for abdominal fat distribution, blood pressure, 75 g oral glucose tolerance test, an intravenous glucose tolerance test followed by a hyperinsulinemic euglycemic clamp and a submaximal exercise test. Results: Offspring exposed to placental malaria during pregnancy had significantly higher 30-minute plasma post-glucose load levels, but no significant difference in peripheral insulin resistance, insulin secretion or other cardiometabolic traits compared with non-exposed individuals. Conclusions: Using the state-of-the-art euglycemic clamp technique, we were unable to prove our a priori primary hypothesis of peripheral insulin resistance in young adult offspring of pregnancies affected by malaria. However, the subtle elevations of plasma glucose might represent an early risk marker for later development of type 2 diabetes if combined with aging and a more obesogenic living environment.